PENDIDIKAN KESEHATAN PADA REMAJA YANG MENGALAMI INSOMNIA DENGAN CARA MENGELOLA STRES - Ida Wahyuni; Willi Holis; Ni Made Dwi Astarina Prajayanti (LPPM STAI Muhammadiyah Probolinggo, 2026)
Introduction: Adolescents are vulnerable to stress due to academic demands, social relationships, and excessive technology use, which can lead to sleep disorders such as insomnia. This condition may affect mental health, learning concentration, and overall quality of life. Methods: This study employed a descriptive analytic design with a cross-sectional approach. The sample consisted of 50 students from SMA Al-Islamiyah Pamekasan selected using total sampling. The instruments used were the KSPBJ-IRS questionnaire to measure insomnia and the DASS-42 to assess stress levels. Data were analyzed using univariate and bivariate analysis with the Pearson chi-square test. Results: The results showed that most respondents experienced mild insomnia (50%) and high levels of stress (60%). After the implementation of health education, there was an improvement in adolescents’ knowledge and skills in managing stress, as well as a better understanding of the relationship between stress and sleep quality. Discussion: Stress plays a significant role in the occurrence of insomnia among adolescents. Health education is proven to be an effective intervention in improving stress management skills through relaxation techniques, time management, and sleep hygiene, thereby potentially enhancing sleep quality and overall quality of life.